Oxidation-Reduction Properties of Chloroplast Thioredoxins, Ferredoxin:Thioredoxin Reductase, and Thioredoxin f-Regulated Enzymes - Hirasawa, Masakazu; Schürmann, Peter; Jacquot, Jean-Pierre; Manieri, Wanda; Jacquot, Pierre; Keryer, Eliane; Hartman, Fred C.; Knaff, David B. (My University, 1999)
Oxidation-reduction midpoint potentials were determined, as a function of pH, for the disulfide/dithiol couples of spinach and pea thioredoxins f, for spinach and Chlamydomonas reinhardtii thioredoxins m, for spinach ferredoxin:thioredoxin reductase (FTR), and for two enzymes regulated by thioredoxin f, spinach phosphoribulokinase (PRK) and the fructose-1,6-bisphosphatases (FBPase) from pea and spinach. Midpoint oxidation-reduction potential (Em) values at pH 7.0 of −290 mV for both spinach and pea thioredoxin f, −300 mV for both C. reinhardtii and spinach thioredoxin m, −320 mV for spinach FTR, −290 mV for spinach PRK, −315 mV for pea FBPase, and −330 mV for spinach FBPase were obtained. With the exception of spinach FBPase, titrations showed a single two-electron component at all pH values tested. Spinach FBPase exhibited a more complicated behavior, with a single two-electron component being observed at pH values ≥ 7.0, but with two components being present at pH values <7.0. The slopes of plots of Em versus pH were close to the −60 mV/pH unit value expected for a process that involves the uptake of two protons per two electrons (i.e., the reduction of a disulfide to two fully protonated thiols) for thioredoxins f and m, for FTR, and for pea FBPase. The slope of the Em versus pH profile for PRK shows three regions, consistent with the presence of pKa values for the two regulatory cysteines in the region between pH 7.5 and 9.0.